Serological and immuno-histopathological detection of Paramphistomum epiclitum infection in large ruminant population in Punjab, Pakistan - KHAN, I; AFSHAN, K; ULLAH, R; KOMAL, M; KHAN, MA; FIRASAT, S (Journal of the Hellenic Veterinary Medical Society, 2021)
Recent molecular identification of Paramphistomum epiclitum in Pakistan raises concerns about its epidemiology and pathologies in infected tissues of ruminants. The present study aimed to find the seroepidemiological and histopathological record of Paramphistomum epiclitum from cattle and buffaloes. Indirect ELISA on animal sera and histology of infected rumen with hematological and biochemical analyses were performed. The overall prevalence of P. epiclitum was noted as 15.3% in the abattoir survey and 37.6% in the serological examination. The sensitivity and specificity of the diagnostic test were 100% and 83.3% respectively. The paramphistomosis was significantly (p= 0.001) higher during August (6.4%) followed by September (5.4%), whereas the lowest prevalence was recorded during April (0.4%). The hematological and biochemical variations showed significant increase in total leukocyte count (p= 0.002), alanine aminotransferase (p= 0.05), glucose (p= 0.01) and cholesterol (p = 0.024) levels. However, significant decrease in the level of erythrocyte (p= 0.019), hemoglobin (p= 0.001), mean corpuscular haemoglobin concentration (p= 0.05), mean corpuscular volume (p= 0.038) and platelets count (p= 0.048) was observed. The histopathology of rumen tissue showed haemorrhages, atrophy of ruminal papillae, sloughed mucosa, cellular vacuolation, and infiltration of lymphocytes inflammatory cells. The present study provides the prevalence and histopathological record of P. epiclitum in Pakistan for the first time in order to take control measures in the country.